RATIO RATIO ANALYSIS FINANCIAL STATEMENTS FINANCIAL INSTITUTIONS sharia, Baitul Maal WATAMWIL BMT "MUBAARAK" MARKET Argosari, Wonosari, DISTRICT GUNUNGKIDUL. PERIOD 2005 - 2007 - One, Mujiyana; one, Drs. Supardi, MM. (Accounting, 2009)
This study aims to determine (1) The ability of Islamic Financial Institutions BMT Mubaarak in meeting short-term liabilities (2) The Efficiency of Financial Institutions Syariah BMT Mubaarak in using its own funds (3) The level of effectiveness achieved by the financial institution of Sharia. BMT Mubaarak through its operating business (4) Efficiency Operational Performance Islamic Financial Institutions. BMT Mubaarak. Data collection using observation techniques, interviews and documentation. The method of analysis used descriptive analysis of the collection and arrangement of data and then analyze and interpret the data is classified The results of this study indicate that the Islamic Financial Institutions. BMT Mubaarak viewed keseluruan of financial reporting data that has last (financial statement data end in 2005, 2006 and 2007) are in good health, is also supported by the statement (PINBUK) Small Business Incubation Center stating that BMT in the healthy category. Keywords : ratio analysis financial,